Cellulose nanofibers from banana rachis added to a Curcuma longa L. rhizome suspension: Color, stability and rheological properties. (January 2021) - Serpa Guerra, A.M.; Gómez Hoyos, C.; Velásquez-Cock, J.A.; Gañán Rojo, P.; Eceiza, A.; Urbina, L.; Zuluaga, R.
Graphical abstract: Highlights: Cellulose nanofibers (CNFs) were added in a 30 wt.% turmeric suspension. CNFs increased suspensions viscosity and the L* coordinate of color. The addition of 0.9 wt% of CNFs allowed the stabilization of turmeric suspension. CNFs form an entangled network that support insoluble phase of the suspension. Abstract: Curcuma longa (CL) rhizome is used for the extraction of curcumin; however, this compound represents only approximately 3% w/w of the dried rhizome. To use the entire rhizome as a food colorant, the development of CL suspensions has been identified. However, since vegetable suspensions are unstable, the present investigation evaluates the influence of the addition of cellulose nanofibers (CNFs) from banana rachis to a CL suspension (30 % w/w). Different concentrations of CNFs were studied (0.1, 0.3, 0.5, 0.7 and 0.9 % w/w). The suspensions obtained were characterized through infrared spectroscopy and determination of curcumin content, color, particle size distribution, stability index (SI), microstructure and rheological properties. The results established that processing of the suspension does not affect the curcumin content, although an increase in the L color coordinate was observed, caused by light scattering, associated with the size of the CNFs. Additionally, we found that 0.1 % w/w CNF had no effect on the stabilization of the CL suspensions; at this concentration, SI was similar to the suspension without CNFs. This behavior allows us to say that the formation of the three-dimensional network of the nanocellulose at this concentration is not effective. As the CNF concentration increases, SI grows, and a 100 % stable suspension up to 30 days is formed by adding 0.9 % w/w CNF. The suspensions without CNFs and with 0.1 % w/w CNF presented similar rheological properties, while the other suspensions were characterized by an increment in consistency and higher values of G' than G", indicating that those suspensions are soft gels.